(untitled) (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This research aims to find out the correlation between students’ reading habits and reading comprehension among second-year students of the English Study Program at FKIP Universitas Riau. Employing a correlational quantitative design, the research involved 38 students from Class 4A selected through purposive sampling, while Class 4C was used for the instrument try-out. Data were collected using two research instruments: The questionnaire was used to gather data on the students’ reading habits, while the test was administered to assess their reading comprehension ability. Data were analyzed using IBM SPSS Statistics 24. The results showed that the mean score of students’ reading habits was 72.21, while the mean reading comprehension score was 80.43. Pearson Product-Moment correlation analysis indicated a moderate negative correlation between the two variables (r = -0.538, p = 0.000), which is statistically significant. The coefficient of determination (R²) was calculated to be 28.9%, indicating that reading habits account for 28.9% of the variance in reading comprehension scores. The findings suggest that although students generally possess adequate reading habits, the types of materials and purposes of reading may significantly influence their comprehension outcomes. Therefore, reading habit development should be accompanied by academic reading strategy training and material selection that aligns with educational objectives.